Tolvaptan use in children and adolescents with autosomal dominant polycystic kidney disease: rationale and design of a two-part,randomized, double-blind, placebo-controlled trial - Schaefer, Franz; Mekahli, Djalila (European journal of pediatrics, 2019)
This report describes the rationale and design of a study assessing tolvaptan in children with autosomal dominant polycystickidney disease (ADPKD). Phase A is a 1-year, randomized, double-blind, placebo-controlled, multicenter trial. Phase B is a 2-year, open-label extension. The target population is at least 60 children aged 12–17 years, diagnosed by family history and/orgenetic criteria and the presence of≥10 renal cysts, each≥0.5 cm on magnetic resonance imaging. Subjects will be allocated into4 groups: females 15–17 years; females 12–14 years; males 15–17 years; and males 12–14 years. Up to 40 subjects aged 4–11 years may also enroll, provided they meet the entry criteria. Weight-adjusted tolvaptan doses, titrated once to achieve atolerated maintenance dose, and matching placebo will be administered twice-daily. Assessments include spot urine osmolalityand specific gravity (co-primary endpoints), height-adjusted total kidney volume, estimated glomerular filtration rate, pharma-codynamic parameters (urine volume, fluid intake and fluid balance, serum sodium, serum creatinine, free water clearance),pharmacokinetic parameters, safety (aquaretic adverse events, changes from baseline in creatinine, vital signs, laboratory valuesincluding liver function tests), and generic pediatric quality of life assessments.Conclusion: This will be the first clinical study to evaluate tolvaptan in pediatric ADPKD.
Published online 3 May 2019
Gesehen am 22.10.2019